Making internal feedback explicit: exploiting the multiple comparisons that occur during peer review. Issue 3 (11th April 2022) - Nicol, David; McCallum, Suzanne
Abstract: This article explores peer review through the lens of internal feedback. It investigates the internal feedback that students generate when they compare their work with the work of peers and with comments received from peers. Inner feedback was made explicit by having students write an account of what they were learning from making these different comparisons. This allowed evaluation of the extent to which students' self-generated feedback comments would match the feedback comments a teacher might provide, and exploration of other variables hypothesized to influence inner feedback generation. Analysis revealed that students' self-generated feedback became more elaborate from one comparison to the next and that this, and multiple simultaneous comparisons, resulted in students' generating feedback that not only matched the teacher's feedback but surpassed it in powerful and productive ways. Comparisons against received peer comments added little to the feedback students had already generated from comparisons against peer works. The implications are that having students make explicit the internal feedback they generate not only helps them build their metacognitive knowledge and self-regulatory abilities but can also decrease teacher workload in providing comments.